Asymmetric Synthesis of Highly Functionalized Tetrahydropyrans via a One-Pot Organocatalytic Michael/Henry/Ketalization Sequence - Hahn, Robert (Org Lett, 2014)
A diastereo- and enantioselective Michael/Henry/ketalization sequence to functionalized tetrahydropyrans is described. The multicomponent cascade reaction uses acetylacetone or β-keto esters, β-nitrostyrenes, and alkynyl aldehydes as substrates affording tetrahydropyrans with five contiguous stereocenters. Employing a bifunctional quinine-based squaramide organocatalyst, the title compounds are obtained in moderate to good yields (27–80%), excellent enantiomeric excesses (93–99% ee), and high diastereomeric ratios (dr > 20:1) after one crystallization. [Image: see text]